Efektivitas Pendekatan Team Teaching terhadap Disiplin dan Fokus Belajar Siswa di Kelas II MI Unggulan Al Muhammad Cepu (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2023)
The team teaching approach in madrasah ibtidaiyah (MI) is often considered effective in improving the quality of learning, but empirical evidence on its impact on student discipline and focus is still limited in the context of basic Islamic education. This study uses a qualitative design of a case study in class II of MI Unggulan Al Muhammad Cepu. Primary data sources include participant observations, in-depth interviews with two teachers of the teaching team and six purposive students, as well as secondary data such as collaborative lesson plans and teacher reflections. The purpose of the study is to analyze the effectiveness of team teaching in improving student discipline and focus on learning. The results showed that the symbiotic-asymmetrical collaboration between the Core Guides and the Response Facilitators created a pauseless instructional flow, reduced extrinsic cognitive load (time-on-task by an average of 85%), and transformed the discipline from external control to relational-proactive co-regulation that is in line with Islamic ta'dib. These findings have practical implications for MI teacher training.